Gender Diversity, Gender in the Boardroom and Gender Quotas - Astrid Kunze; Katrin Scharfenkamp (Center for Economic Studies and ifo Institute (CESifo), 2022)
This study investigates boards of (non-executive) directors and whether employee representation has a positive effect on gender diversity on boards. We exploit rich, newly assembled board–director matched panel data for Norway and Germany, which contain unique information on whether a director represents shareholders or employees during the period around 2008, when a Norwegian board gender quota came into effect. We present two novel results that challenge previous thinking about the effects of board gender quotas on women directors. First, we find a positive impact of employee representation before the gender quota reform on gender diversity. Second, although the Norwegian gender quota has increased the probability of a director being female, the effect through employee representation has relatively decreased after the implementation of the reform. We discuss potential mechanisms and implications for the design of co-determination laws and gender quotas.
Keywords: G30; J16; K30; L21; L25; M54; 330; affirmative action; employee representation; shared governance; co-determination; women; boards of directors; firm size